Effect of Wavelet Compression of High Frequency Time Series on the Quality of Information and Prediction - Korczak, Jerzy; Drelczuk, Krzysztof (Wpływ kompresji szeregów czasowych o dużej częstotliwości falką Daubeuchies 4 na jakość zawartych w nich informacji, 2010)
In recent times research work on the use of wavelet theory in data mining has increased significantly. In most cases, these works relate to specific applications. In this paper the general compression method of time series will be presented and adapted to financial time series analysis where dimensionality reduction is crucial. This hypothesis proposes that a double compression using Daubechies 4 wavelet does not significantly affect the quality of information carried by a time series. The reduction of dimensionality significantly affects the algorithmic complexity and improves its quality of prediction. In order to verify this hypothesis the highly frequent time series will be evaluated in terms of forecasting quality where future value is predicted only on the basis of the past quotations. In this project as a predictive algorithm we used ARAR due to its good results in forecasting of the real financial time series.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 104, s. 99-113
Keywords: time series analysis; discrete wavelet transform; Daubechies 4; prediction